The State Confessional Policy in Russia - I. V. Kolosova (Проблемы постсоветского пространства, 2024)
The article considers the evolution of the state confessional policy in Russia. It explores the genesis of the state religious policy in the period of existence of the multi-confessional Russian Empire, highlights the special features of the religious politics and atheistic propaganda in the USSR, the transformation of the state confessional policy during the years of perestroika and after the dissolution of the Soviet Union. The features of the religious renaissance on the post-Soviet space are being observed as well as the process of formation of the contemporary model of the state confessional policy in Russia. Special attention is paid to the development of the legal base for interaction of the state authorities and religious confessions and to the state structures which provide communication with religious organizations. The main areas of co-operation of the state with the traditional religions of Russia are being explored. Special attention is paid to the activities of the Interreligious Council of Russia and of the Interreligious Council of the CIS.